Participatory Leadership and Teacher Motivation in Improving School Quality - Muhammad Anggung Manumanoso Prasetyo; Wirdatul Kifla (Tarbiyah Departement collaboration with AMCA, 2023)
This study describes the effect of participatory leadership and teacher work motivation on school quality. This study uses a quantitative paradigm of survey methods. This research was conducted on teachers at MIN 26 Aceh Utara. The population is 30 with a total sampling technique. Data was collected through a questionnaire with a Likert scale. Data analysis using regression analysis started with descriptive analysis, calculation of the prerequisites of analysis (normality, linearity, and homogeneity), and continued with hypothesis testing. The results of the analysis show that there are: (1) The direct effect of participatory leadership on school quality is significant, based on the level of significance (Sig = 0.000) and the correlation coefficient of 85.3%; (2) teachers' work motivation on school quality with a correlation coefficient of 64.2%; (3) participatory leadership and teacher work motivation simultaneously affect school quality by 86%. This study concludes that participatory leadership and teacher work motivation affect school quality. The implication is that more effective participatory leadership and high work motivation of teachers will affect the increasing quality of schools.